PENGEMBANGAN EKONOMI WILAYAH BERBASIS SEKTOR PERIKANAN DI PROVINSI JAWA TIMUR - S. Sulistiyanti; W. Wahyudi (MediaTrend, 2015)
The fisheries sector is one sector of the economy that became the foundation of life of many residents, especially fishermen. One strategy that is done for the development of this sector is the minapolitan concept, where fisheries and marine sector became the driving force of the economy in the Minapolitan.This study intends to examine whether the fisheries sector is a sector - basis which can be developed without constrained by the capacity of the local economy - in areas designated as Minapolitan. Furthermore, this study also intends to find out whether the factors that drives the development of the fisheries sector, so expect the resulting findings can serve as a reference for decision makers in the field of fisheries.Results of research by using location quotient (LQ), found that almost all regenciesMinapolitan really have the advantage in the fisheries sector. However there are some areas that do not excel in this sector when viewed from the LQ coefficient. The area in question is Malang, Tulungagung, Pasuruan and Tuban Region. By using regression methods, can be found that fisheries production is influenced significantly by the number of fishermen, boats and outboard motor boats. The factors that most influence are motorboats. As for the production of farmed fish, is affected by the number of fish farmers and land cultivation. The most instrumental factor in the development of farmed fish is a fish farmer.